Durnamai-yi falakat va i'itilai-yi nuvini inqilab : (Danishjuyani Havadari Ittihadi Mubarizani Kumunist dar Almani Fidral va Birlini Gharbi)
The prospective of calamity and the rise of the new revolution; theses on the political significance of the economic crisis.